2020
DOI: 10.1186/s12870-019-2196-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis indicates that a core transcriptional network mediates isonuclear alloplasmic male sterility in wheat (Triticum aestivum L.)

Abstract: Background: Cytoplasmic male sterility (CMS) plays a crucial role in the utilization of heterosis and various types of CMS often have different abortion mechanisms. Therefore, it is important to understand the molecular mechanisms related to anther abortion in wheat, which remain unclear at present. Results: In this study, five isonuclear alloplasmic male sterile lines (IAMSLs) and their maintainer were investigated. Cytological analysis indicated that the abortion type was identical in IAMSLs, typical and sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…In plants, inositol phosphate and phenylalanineinduced transcripts and their osmoregulation mechanisms were reported in response to heat stress [70][71][72]. Extensively studied genes in plants include induced expression of cytochrome P450 genes involved in the biosynthesis of indole alkaloid as well as other secondary metabolites and glycerolipid-and glycerophospholipid-induced transcripts in lipid metabolism under heat stress and their mechanisms in response to heat stress [73][74][75]. The unique metabolic pathways in V. darrowii are carbon fixation, pyruvate, amino sugar, nucleotide sugar, galactose, glyoxylate and dicarboxylate, fructose and mannose metabolism, other glycan degradation, and nitrogen metabolism ( Figure 5C,D).…”
Section: Dynamics Of Key Pathways Involved In Response To Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, inositol phosphate and phenylalanineinduced transcripts and their osmoregulation mechanisms were reported in response to heat stress [70][71][72]. Extensively studied genes in plants include induced expression of cytochrome P450 genes involved in the biosynthesis of indole alkaloid as well as other secondary metabolites and glycerolipid-and glycerophospholipid-induced transcripts in lipid metabolism under heat stress and their mechanisms in response to heat stress [73][74][75]. The unique metabolic pathways in V. darrowii are carbon fixation, pyruvate, amino sugar, nucleotide sugar, galactose, glyoxylate and dicarboxylate, fructose and mannose metabolism, other glycan degradation, and nitrogen metabolism ( Figure 5C,D).…”
Section: Dynamics Of Key Pathways Involved In Response To Heat Stressmentioning
confidence: 99%
“…Photosynthesis enhancement by ameliorating glyoxylate and dicarboxylate metabolism genes and their induced transcripts are involved in the comprehensive regulation of photosynthetic carbon metabolism under heat stress [37,70,77]. Previous studies reported fructose and mannose metabolism gene expression in response to heat stress and their osmoregulation [74,78].…”
Section: Dynamics Of Key Pathways Involved In Response To Heat Stressmentioning
confidence: 99%
“…Previous studies have shown that the large superfamily ABC transporter proteins are involved in translocation of a broad range of substances across membranes using energy from ATP hydrolysis such as transport of sporopollen (the main component of pollen exine) so they are also required for pollen exine formation (Chang et al, 2018). The tapetum provides sucrose, proteins, lipids, and sporopollenin to support the growth and development of the pollen via its degradation and secretion, and the progress of secreting nutrients to pollen is considered to be vesicular trafficking (Liu et al, 2020). Here, vesicular trafficking related DEGs encoding Sec23/Sec24 trunk domain protein, coatomer WD .…”
Section: Effects Of Altered Alternative Splicing and Gene Expression mentioning
confidence: 99%
“…In CMS lines wheat, premature or delayed PCD by tapetal cells disorganized the supply of the nutrients to microspores, thereby resulting in pollen abortion (Meng et al, 2016). Previous studies suggested this irregular tapetal PCD was tightly controlled by evolutionarily conserved transcriptional cascades (Liu et al, 2020). In recent years, hybrid breeding has a remarkable success in several allogamous species such as maize, sunflower, sorghum, sugar beet, and rye, but not be fully exploited in autogamous crops (Longin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, RNA sequencing (RNA-Seq) has been applied for the key genes and vital metabolic pathway networks in a strong instrument. For example, soybean [17], rice [18], cotton [19], cabbage [20], wheat [21] and rice [22].…”
Section: Introductionmentioning
confidence: 99%